GDSL Lipase Gene HTA1 Negatively Regulates Heat Tolerance in Rice Seedlings by Regulating Reactive Oxygen Species Accumulation - Rui Su; Jingkai Luo; Yingfeng Wang; Yunhua Xiao; Xiong Liu; Huabing Deng; Xuedan Lu; Qiuhong Chen; Guihua Chen; Wenbang Tang; Guilian Zhang (MDPI AG, 2024)
High temperature is a significant environmental stress that limits plant growth and agricultural productivity. GDSL lipase is a hydrolytic enzyme with a conserved GDSL sequence at the N-terminus, which has various biological functions, such as participating in plant growth, development, lipid metabolism, and stress resistance. However, little is known about the function of the GDSL lipase gene in the heat tolerance of rice. Here, we characterized a lipase family protein coding gene HTA1, which was significantly induced by high temperature in rice. Rice seedlings in which the mutant hta1 was knocked out showed enhanced heat tolerance, whereas the overexpressing HTA1 showed more sensitivity to heat stress. Under heat stress, hta1 could reduce plant membrane damage and reactive oxygen species (ROS) levels and elevate the activity of antioxidant enzymes. Moreover, real-time quantitative PCR (RT-qPCR) analysis showed that mutant hta1 significantly activated gene expression in antioxidant enzymes, heat response, and defense. In conclusion, our results suggest that HTA1 negatively regulates heat stress tolerance by modulating the ROS accumulation and the expression of heat-responsive and defense-related genes in rice seedlings. This research will provide a valuable resource for utilizing HTA1 to improve crop heat tolerance.